O papel das células T reguladoras na diabetes mellitus tipo 1 - Margarida Silvina de Freitas Vieira (2020)
Type 1 diabetes (T1D) is an autoimmune disease caused by a shift from the balance of regulatory T cells (Tregs), that control immune tolerance and modulate the autoimmune response, and effector T cells, which become autoreactive, leading to massive destruction of the pancreatic islets beta cells. T1D is one of the most frequent chronic diseases in the world, with increasing incidence and prevalence ratios over the years. However, the treatments currently available for T1D do not cure the disease, causing a high prevalence of patients who still progress into severe complications and therefore having higher morbidity and mortality rates. The medical area is evolving each day into personalized treatments, specific for every patient and for each disease. The papers on autoimmune diseases, namely T1D, show that this area is no exception. Therapies that target specific cellular changes in T1D patients are rapidly emerging, particularly focusing on restoring the imbalance caused by Tregs dysfunction. This group of cells express some cellular markers on the surface that distinguish them from the other cells of the immune system. Therefore, they are also referred to as CD4+ CD25+ CD127- FOXP3+ cells. In this review, we examine the work of several authors on the role of these markers in Tregs function and thus, on T1D progression, as well as their potential as clinical treatments for this disease. A new promising area of investigation has emerged with the isolation and expansion of autologous Treg from T1D patients, using factors that enhance their growth and efficacy in vitro. They are then infused into the patients' bloodstream to increase the number of Tregs that can fight the underlying autoimmune imbalance of the body. Authors have also been working on identifying which antigens better help select the group of Tregs that act preferentially in the pancreatic islets, in order to obtain a more adapted and selective Treg treatment for T1D. The different techniques developed so far, as well as future recommendations and limitations from these studies will be addressed in this review.